2018
DOI: 10.1039/c8ta03509a
|View full text |Cite
|
Sign up to set email alerts
|

A nanosized metal–organic framework with small pores for kinetic xenon separation

Abstract: The crystal size of CaSDB metal–organic framework has been engineered down to nanoscale by an additive-assisted method. The as-prepared material has exhibited superior xenon capture performance in terms of fast xenon uptake and good selectivity for xenon over krypton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Recently, considerable efforts have focused on exploring the nanoscale synthesis of metal-organic frameworks (nano-MOFs) due to the promise of their heightened performance in drug delivery, [11][12][13] catalysis, 14 membrane design for gas storage and separation, [15][16][17] and analyte sensing. 18 As 3D porous coordination polymers comprised of inorganic clusters bridged by multi-topic organic linkers, MOFs display immense modularity that has given rise to more than 20 000 unique bulk phases, 19 each with the potential to adopt enhanced functionalities when prepared as nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable efforts have focused on exploring the nanoscale synthesis of metal-organic frameworks (nano-MOFs) due to the promise of their heightened performance in drug delivery, [11][12][13] catalysis, 14 membrane design for gas storage and separation, [15][16][17] and analyte sensing. 18 As 3D porous coordination polymers comprised of inorganic clusters bridged by multi-topic organic linkers, MOFs display immense modularity that has given rise to more than 20 000 unique bulk phases, 19 each with the potential to adopt enhanced functionalities when prepared as nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) constructed from organic linkers and metal clusters are promising materials for photocatalytic application, owing to their tunable character in structure and property. More importantly, there might be various photoinduced charge/energy transfer processes in MOFs, such as metal-to-ligand charge transfer, ligand-to-ligand energy transfer, ligand-to-metal charge transfer, and so forth. These processes are important and essential for MOF-mediated photocatalytic reactions. The rapid development of MOFs has generated intense photocatalysis studies in which MOFs have been generally applied as heterogeneous photocatalysts to drive desirable photochemical reactions. Recently, the use of MOFs to carry out photoinduced organics transformation has attracted increasing attention. Emerging studies have demonstrated that MOFs are intriguing photocatalysts for oxidizing reactions. Zeng et al reported the aerobic oxidation of benzylamines and benzylalcohols over a perylene-diimide-based coordination polymer .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid deprotonation and nucleation at higher pH and the inhibitory effect of capping groups on the growth produce MOFs with small crystals. [ 57 ] Small‐molecule acids are commonly used as capping reagents, including hydrofluoric acid (HF), [ 58 ] acetic acid, [ 59 ] lauric acid, [ 60,61 ] benzoic acid, [ 62 ] salicylic acid, [ 43 ] and fumaric acid. [ 63 ] As a representative example, Guo et al.…”
Section: Synthesis Strategies Of Nanoscale Metal‐organic Frameworkmentioning
confidence: 99%